Can Bitcoin Mining Increase Renewable Electricity Capacity? - August Bruno; Paige Weber; Andrew J. Yates (Center for Economic Studies and ifo Institute (CESifo), 2022)
Proponents of Bitcoin argue that demand for electricity from Bitcoin miners can lead to an increase in renewable electricity capacity. We rigorously evaluate this claim by estimating a Bitcoin electricity demand curve and include this demand curve in a long-run model of the Texas electricity market. We find that while Bitcoin mining can indeed increase renewable capacity, it also increases carbon emissions. When Bitcoin miners provide grid management services in the form of demand response, their emissions impact is largely mitigated.
Keywords: Q49; Q42; Q41; 330; cryptocurrency; electricity markets; renewable energy; Bitcoin